Long term outcome of surgical treatment of fractures of pelvis - Ajai Singh (Journal of Orthopedics, Traumatology and Rehabilitation, 2014)
With the advances in the trauma management, the protocol of the treatment of fractures of pelvis has evolved with control of mortality and morbidity, which is associated with these fractures. The goal of management is to achieve anatomical reduction with stable fixation of these fractures with optimum functional outcome. Despite of the better understanding of the pathophysiology of these fractures and advances in the surgical techniques to fix these fractures, the long term outcomes of these fractures are not predictable. Though in majority of patients, we may achieve the pelvic stability and pain free walking, but still we are not able to define a reproducible approach to achieve the optimum functional outcomes in all the patients with fractures of pelvis. The present paper deals with a systematic review of available literature related with controversies related with all aspect of surgical treatment of these fractures including various methods of management, various methods of fixation, techniques of fixation, determination of type and amount of pelvic stablisation and evaluation of long term functional outcome and its correlation with various factors.